The Effects of Ascorbic Acid and U-74389G on Renal Ischemia-Reperfusion Injury in a Rat Model - ZOGRAFOS, CONSTANTINOS G. (In Vivo, 2020)
Background/Aim: U-74389G and ascorbic acid protect the cells from oxidation. This study aimed to depict their role in ischemia–reperfusion injury in a renal rat model. Materials and Methods: Sixty Wistars rats were randomized into six groups of 10 animals each. Group A Ischemia 30 min, reperfusion 60 min; Group B Ischemia 30 min, reperfusion 120 min; Group C Ischemia 30 min, ascorbic acid administration, reperfusion 60 min; Group D Ischemia 30 min, ascorbic acid administration, reperfusion 120 min; Group E Ischemia 30 min, U-74389G administration, reperfusion 60 min; Group F Ischemia 30 min, U-74389G administration, reperfusion 120 min. We then collected tissue and blood samples. Results: Histology and the significantly decreased malondialdehyde and tumor necrosis factor-α levels indicated that ascorbic acid was superior to U-74389G, at pre-defined time intervals. Conclusion: Ascorbic acid and U-74389G ameliorated renal damage induced by ischemia–reperfusion injury, suggesting a therapeutic effect.